Implementing Collaborative Learning to Promote Inference-Making in a Reading Strategy Course in English - Adriana Murillo Rojas; Juan Pablo Zúñiga Vargas (Revista de Lenguas Modernas, 2017)
This article reports on the ndings of a research project intended to promote collaborative learning and inference-making among students from majors other than English at the University of Costa Rica. First, a diagnosis was carried out to know the students’ previous knowledge about inferences. Second, a strategy consisting of various stages was implemented for students have a better understanding of inference- making and have collaborative practice to make inferences. The results indicate that many students fail to see the difference between paraphrasing and making inferences even though they can clearly de ne what an inference is. After the implementation of the strategy, most students concurred that they feel more con dent about making inferences in English and saw the value of the instruction given.